Magnetoencephalography in a virtual environment - Roberts, Gillian (2020)
Magnetoencephalography (MEG) is a functional neuroimaging technology which allows researchers to probe brain activity with fine-grained temporal and spatial resolution. By measuring the femtotesla-scale magnetic fields produced by neural currents, the underlying distribution of these currents can be estimated, enabling maps of brain electrophysiology to be constructed. The magnetic field detector employed in extant MEG systems is the superconducting quantum interference device (SQUID), which exploits low-temperature quantum phenomena to detect extremely weak magnetic fields. In this thesis, we describe a new type of wearable MEG scanner based on optically pumped magnetometers (OPMs). These devices can measure magnetic fields with the requisite sensitivity and bandwidth for MEG signal detection, while their cryogen-free design vastly increases their flexibility compared to SQUIDs. We describe the fabrication of a bespoke scalp-mounted OPM array, designed to make MEG measurements while the participant is permitted a significant degree of head movement (±10 cm). One facet of OPM array design is the investigation of crosstalk effects between sensors; in the process of field measurement, a sensor produces small magnetic fields which may leak into proximal sensors, altering gain and sensitive direction. We explore this issue in detail, beginning with the OPM signal equations to formulate a model of crosstalk generation in OPMs. We provide experimental evidence to support this model, and investigate the detrimental effects of uncorrected crosstalk on neural source estimation. The high flexibility of our scalp-mounted array motivated the investigation of more naturalistic experimental paradigms which exploit the newly possible degree of participant movement. In particular, this thesis describes a set of experiments which combine virtual reality (VR) technology with the OPM array, allowing us to record MEG data while a participant is immersed in a virtual environment. The integration of the HMD with the MEG system introduced a degree of magnetic interference to the MEG data; however, by employing synthetic gradiometry, we were able to significantly cancel fields from the HMD, permitting adequate signalto-interference ratio to detect and localise neural responses. Our combined VRMEG apparatus allowed us to provide the participant with realistic environments, enabling a decision-making paradigm which involved responding to the action of a virtual human avatar. Lastly, we describe an experiment in which we measured the magnetic fields generated by the head-mounted display, observing the magnetic field patterns produced by currents in the organic light-emitting diode (OLED) elements of the screen. This experiment is the first step towards a generative model of magnetic field interference in the HMD, which could lead to an interference-free VR-MEG system. Some other possible avenues of development, including external projector-based VR, are evaluated for use with OPM-MEG.